Applied passive acoustic monitoring of South Africa's most threatened marine mammal, the Indian Ocean humpback dolphin (Sousa plumbea) - Dines, Sasha Francess (Stellenbosch : Stellenbosch University, 2025)
Thesis (PhD)--Stellenbosch University, 2025.